Localization and Cultural Ecotourism: Pa Kham Chanod Area - Charoenmahavit, Benjapak (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2020)
This article focuses on the local tourism adaptation that has been affected by globalization. Pa Kham Chanod area and cultural ecotourism culture were used as a case study. This study is conducted by document research. The study indicated that the locality had adapted by means of the community constructed a sacred space from the legend, beliefs, and myths that had been told since the past to be a framework for ecotourism and culture for tourists to follow, based on their beliefs and beliefs in the sacred area, resulting in the Kam Chanod area be able to maintain the ecological and cultural resources that exist until now.